2016
DOI: 10.1177/0162643416651724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Augmented Reality to Complete a Chain Task for Elementary Students With Autism

Abstract: The purpose of this study was to examine the effects of augmented reality to teach a chain task to three elementary-age students with autism spectrum disorders (ASDs). Augmented reality blends digital information within the real world. This study used a marker-based augmented reality picture prompt to trigger a video model clip of a student brushing her teeth. All students learned how to brush their teeth independently and maintained the skill 9 weeks later with the introduction of augmented reality. Theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 38 publications
(45 reference statements)
2
62
0
1
Order By: Relevance
“…This review analyzed and selected twenty studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Thirteen were single subject designs [ 24 , 26 , 27 , 28 , 30 , 31 , 32 , 36 , 37 , 38 , 39 , 40 , 41 ]. Five of them were multiple baseline design [ 24 , 26 , 27 , 31 , 32 ], and seven were group design studies [ 25 , 29 , 33 , 34 , 35 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review analyzed and selected twenty studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Thirteen were single subject designs [ 24 , 26 , 27 , 28 , 30 , 31 , 32 , 36 , 37 , 38 , 39 , 40 , 41 ]. Five of them were multiple baseline design [ 24 , 26 , 27 , 31 , 32 ], and seven were group design studies [ 25 , 29 , 33 , 34 , 35 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…To support children with autism to independently learn chaintasks, Cihak et al [16] developed an AR application on a handheld device. In a study, three autistic children used the application to learn brushing their teeth.…”
Section: Childrenmentioning
confidence: 99%
“…Retrospectively, we consider that these data could have provided even better insight into our findings; (b) we used an alphabetic letter and number task, however, the improvement in touching those symbols could not be linked with literature level and learning process. Although some studies using AR applications used the correct scores before and after an intervention 15,18,20 to analyze performance, future studies would be designed to understand the effect of literacy and/or numeracy in learning (reading level, writing ability, ability to identify alphabetic letters and numbers), and (c) the present study included a heterogeneous population with a wide age range and gender difference between groups (it was not possible to analyze gender or age differences). Furthermore, although ASD is considered a heterogeneous condition, and nonsignificant Spearman's correlations were found with independent variables data, a more homogenous sample of participants could provide more specific results.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…15 AR rehabilitation approaches have been growing in recent years promoting increase in selective and sustained attention 16 and active participation in realistic and interactive simulations. 17 This has led to research interests in a range of everyday adaptive living situations, including living tasks, such as brushing their teeth independently, 18 interventions to enhance social communication, 19 and promotion of greeting skills. 20 One significant recent study is that of Guarnieri et al 21 in which an AR game called ''MoviLetrando'' was presented and demonstrated feasibility and reliability in use with 88 intellectually disabled young individuals, together with the game's ability to provide similar and precise results on test-retest trials.…”
Section: Introductionmentioning
confidence: 99%